Cooperative Law as a vacuum in antitrust analysis - the case of health cooperatives in Brazil (2019)
The article seeks to explain some of the probable contributions of Cooperative Law to an integrated analysisof possible antitrust cases involving cooperatives. It is hypothesized that, if on the one hand there is littleknowledge and disclosure about cooperativism in the non-specialized academic sector, there is no a prioriincompatibility between the objectives of cooperative cooperation behavior and the objectives of CompetitionLaw. . On the other hand, the identification of structural parameters of the Cooperative Law and its receptionin the legal system by means of constitutional parameters destined to the exercise of the cooperative activityallow to establish the dialogue of the sources based on the idea of development, which is not limited to themeaning of economic growth. As a demonstration, the consolidated jurisprudence on the possible illegality ofcompetition consisting of some practices in the field of health cooperatives is criticized. Based on the doctrineand legislation, an adapted application of the “escape valves” of the law that structures the Brazilian System ofDefense of Competition (Law 12.529 / 2011) is proposed.